Molecular profiling of angiogenesis in hypericin mediated photodynamic therapy - Bhuvaneswari, Ramaswamy (BioMed Central, 2008)
BACKGROUND: Photodynamic therapy (PDT) involves the administration of a tumor-localizing photosensitizing drug, which is activated by light of specific wavelength in the presence of molecular oxygen thus generating reactive oxygen species that is toxic to the tumor cells. PDT selectively destroys photosensitized tissue leading to various cellular and molecular responses. The present study was designed to examine the angiogenic responses at short (0.5 h) and long (6 h) drug light interval (DLI) hypericin-PDT (HY-PDT) treatment at 24 h and 30 days post treatment in a human bladder carcinoma xenograft model. As short DLI targets tumor vasculature and longer DLI induces greater cellular damage, we hypothesized a differential effect of these treatments on the expression of angiogenic factors. RESULTS: Immunohistochemistry (IHC) results showed minimal CD31 stained endothelium at 24 h post short DLI PDT indicating extensive vascular damage. Angiogenic proteins such as vascular endothelial growth factor (VEGF), tumor necrosis growth factor-α (TNF-α), interferon-α (IFN-α) and basic fibroblast growth factor (bFGF) were expressed to a greater extent in cellular targeting long DLI PDT compared to vascular mediated short DLI PDT. Gene expression profiling for angiogenesis pathway demonstrated downregulation of adhesion molecules – cadherin 5, collagen alpha 1 and 3 at 24 h post treatment. Hepatocyte growth factor (HGF) and Ephrin-A3 (EFNA3) were upregulated in all treatment groups suggesting a possible activation of c-Met and Ephrin-Eph signaling pathways. CONCLUSION: In conclusion, long DLI HY-PDT induces upregulation of angiogenic proteins. Differential expression of genes involved in the angiogenesis pathway was observed in the various groups treated with HY-PDT.